Characterization of the Porcine CLEC12A and Analysis of Its Expression on Blood Dendritic Cell Subsets - Álvarez, Belén; Nieto-Pelegrín, Elvira; Martínez de la Riva, Paloma; Toki, Daisuke; Poderoso, Teresa; Revilla, Concepción; Uenishi, Hirohide; Ezquerra, Angel; Domínguez, Javier (Frontiers in Immunology, 2020)
CLEC12A has been proposed as a suitable target for delivering antigen to dendritic cells (DCs) to enhance vaccine efficacy both in human and mouse. In this study, we have characterized the porcine homolog of CLEC12A (poCLEC12A). Using new monoclonal antibodies (mAb), raised against its ectodomain, poCLEC12A was found to be expressed on alveolar macrophages, blood conventional type 1 and type 2 DCs and plasmacytoid DCs, but not on monocytes, T cells, B cells or NK cells, in contrast to its human and murine homologs. Western blot analysis showed that in alveolar macrophages this receptor is expressed both as a monomer and a dimer. After binding to DCs, anti- poCLEC12A mAb was efficiently internalized. No significant changes were observed in TNFα or IFNα secretion by plasmacytoid DCs stimulated with either CpGs (ODN2216) or polyinosinic-polycytidylic acid (poly I:C), upon incubation with mAb. These results provide the basis for future investigations aimed to assess the ability of anti-poCLEC12A mAbs to improve vaccine efficacy by targeting antigen to DCs.